2011
DOI: 10.1089/tmj.2011.0060
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Tutorial for Parents of Young Children with Autism: Results from a Pilot Study

Abstract: Objective: Early intervention can significantly improve long-term outcomes for children with autism. Unfortunately, many children do not receive early intervention services due to a critical shortage of trained professionals in this area. To bridge this gap, we evaluated a Web-based parent training tutorial (Enhancing Interactions), based on evidence-based practices and utilizing the Web-based platform to maximize learning. Methods: Twenty-three parents with a child between 18 months and 6 years with an autism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 20 publications
0
62
0
1
Order By: Relevance
“…Two studies employed pre-and post-test designs (Hamad, et al, 2010;Kobak et al, 2011). In one study, the researchers conducted a randomised clinical trial (Jang et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies employed pre-and post-test designs (Hamad, et al, 2010;Kobak et al, 2011). In one study, the researchers conducted a randomised clinical trial (Jang et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Three studies evaluated the effects of an Internet-based intervention on the participants' knowledge acquisition related to specific training contents (Hamad et al, 2010;Jang et al, 2012;Kobak et al, 2011). Changes in knowledge were measured by comparing the results of pre-and post-intervention tests.…”
Section: Research Question and Dependent Variablementioning
confidence: 99%
See 2 more Smart Citations
“…Several uncontrolled studies have demonstrated the feasibility, acceptability, and initial effectiveness (i.e., gains in parent knowledge) of self-directed telehealth PMI programs (Hamad et al 2010;Jang et al 2012;Kobak et al 2011). A small RCT (n = 27) found that parents who received a DVD-based self-directed program made greater gains in their use of pivotal response treatment (PRT) strategies, provided more language opportunities, and were rated as displaying greater parent confidence during a 10-min parent-child observation in the home than parents in a no-treatment control group (Nefdt et al 2009).…”
Section: Introductionmentioning
confidence: 99%